Association between vitamin D receptor FokI polymorphism and hypertension in Indonesian ischemic stroke patients: a cross-sectional study - Rizki Arrizal; Cut Aria Arina; Yahwardiah Siregar (Acta Biochimica Indonesiana, 2026)
Background: Vitamin D receptor (VDR) FokI polymorphism (rs2228570) affects VDR protein transcriptional activity and may influence hypertension risk through renin-angiotensin system modulation. However, evidence in Southeast Asian stroke populations remains limited. Objective: To investigate the association between VDR FokI polymorphism and hypertension in Indonesian ischemic stroke patients. Methods: This cross-sectional study enrolled 85 ischemic stroke patients (50 hypertensive, 35 normotensive) from Medan, Indonesia. VDR FokI genotypes (CC, CT, TT) were determined using PCR-RFLP. Association with hypertension was analyzed using chi-square test. Results: Genotype distribution showed CC and CT at equal frequency (44.7% each) and TT at 10.6%, with corresponding C and T allele frequencies of 67.1% and 32.9%, respectively. Among hypertensive stroke patients, CT genotype predominated (52.0%), whereas CC genotype was most prevalent in normotensive patients (57.1%). Despite these distributional differences, no significant association was observed between VDR FokI polymorphism and hypertension (χ² = 3.732, p = 0.155). Conclusion: VDR FokI polymorphism was not significantly associated with hypertension in Indonesian ischemic stroke patients, suggesting that genetic predisposition via this single polymorphism may be overshadowed by established stroke pathophysiology or complex gene-environment interactions in this specific clinical context.